2009
DOI: 10.1038/sj.bjc.6604857
|View full text |Cite
|
Sign up to set email alerts
|

HOX transcription factors are potential therapeutic targets in non-small-cell lung cancer (targeting HOX genes in lung cancer)

Abstract: The HOX genes are a family of homeodomain-containing transcription factors that determine the identity of cells and tissues during embryonic development. They are also known to behave as oncogenes in some haematological malignancies. In this study, we show that the expression of many of the HOX genes is highly elevated in primary non-small-cell lung cancers (NSCLCs) and in the derived cell lines A549 and H23. Furthermore, blocking the activity of HOX proteins by interfering with their binding to the PBX co-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 29 publications
4
101
0
Order By: Relevance
“…13 Our previous study showed that HOXA1, targeted by miR-100, played a role in SCLC cell survival and chemoresistance. 14 HOXA1 was found to stimulate STAT3 and STAT5B in oncogenic transformation of the immortalized mammary epithelial cells, 15 and regulated the p44/42 MAP kinase pathway in mammary cancer cells. 16 The overexpression of HOXA1 was associated with poor outcome in patients with HCC, whereas the downregulation of HOXA1 can inhibit cell growth, anchorage-independent growth, migration, and invasion of HepG2 cells.…”
mentioning
confidence: 99%
“…13 Our previous study showed that HOXA1, targeted by miR-100, played a role in SCLC cell survival and chemoresistance. 14 HOXA1 was found to stimulate STAT3 and STAT5B in oncogenic transformation of the immortalized mammary epithelial cells, 15 and regulated the p44/42 MAP kinase pathway in mammary cancer cells. 16 The overexpression of HOXA1 was associated with poor outcome in patients with HCC, whereas the downregulation of HOXA1 can inhibit cell growth, anchorage-independent growth, migration, and invasion of HepG2 cells.…”
mentioning
confidence: 99%
“…VCP is involved in the regulation of activation of nuclear factor kappa B (NFκB) (Naora et al, 2001;Takahashi et al, 2007), which is a transcription factor correlated with various cellular activities such as anti-apoptosis, and cell proliferation and invasion (Plowright et al, 2009). Univariate analysis revealed that expressions of VCP and PBX2 were significant factors for both DFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Potts et al reported that HOX protein ensures cell survival by inhibition of apoptosis, thus promotes leukemia development (39). Decreased activity of HOX proteins by interfering their binding to the PBX co-factor causes apoptosis of cancer cell lines in vitro and reduces the growth in vivo (15,40).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other HOX proteins, PBX family proteins have not been studied in detail. The interference of PBX binding to HOX proteins yielded apoptosis and reduced growth activity of tumors in vivo, indicating that the interaction of PBX to HOX appears to be crucial in tumor behavior (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%